Comparative study of three methodologies saponins quantitative extraction of melisa officinalis “toronjil” - Flores, T. (2013)
In our research, a phytochemical screening was performed by the method of Cain - Bohmann modified yielding presence of good amount of saponins, which were identified as triterpenoid saponins using qualitative tests that were positive and the test of the foam reaction with the reagent Salwosky, Bouchard Liberman reagent and reaction with sulfuric acid. Three quantitative methods for extracting saponins from a hydroalcoholic extract of the plant and subsequent hydrolysis were developed. The difference of the first two methods was to use a method with the sample defatted with chloroform and the other without scouring . For the third method according to the procedure applied M.E.Wall et al. (1958). Extraction rates for the three methods saponins were 3.90%, 2.40 % and 2.02% respectively. Similarly the corresponding aglycones after acid were obtained by hydrolyzing the crude obtained via.